Salivary IgG and IgA in newborn calves and the possible role in the assessment of passive immunity transfer - Berteselli, G. V.; Filipe, J.; Martelli, A.; Vezzaro, G.; Canali, E.; Dall’Ara, P. (Frontiers in Veterinary Science, 2024)
The transfer of immunoglobulins from the mother to newborns is widely recognized as a critical event for safeguarding offspring against potentially life-threatening infectious diseases. Mainly for this reason, this study aimed to assess the concentrations of immunoglobulin G (IgG) and immunoglobulin A (IgA) in the saliva of newborn calves and explore its potential use as a noninvasive matrix for monitoring passive immunity transfer from cows to calves, as also to evaluate how colostrum intake affects serum and saliva IgG and IgA concentrations. The quality of colostrum samples was evaluated using an optical refractometer before administration to the calves. Saliva and blood samples from 24 calves were obtained at the day of birth (T0) and 2 days after (T2) for determination of serum concentrations of total protein by refractometer, IgG and IgA (both on serum and saliva) by ELISA test. Positive correlations were observed between salivary IgA at T2 and salivary IgG at T2, as well as between serum IgA at T2 and serum protein levels at T2. A significant increase in both IgG and IgA levels in calf serum and saliva was noted. Salivary IgA levels can reflected salivary IgG levels, which, in turn, correlated with serum IgG concentration. These findings suggest the potential utility of IgA in detecting monitoring passive immunity transfer, and support do not exclude saliva as an alternative, practical, and non-invasive matrix for assessing passive immunity transfer.